Kalmyk kinship terminology as a reflection of historical ties and ethnocultural contacts between the Oirat world and Tuvans - Popov, Vladimir A.; Burykin, Aleksey A. (The New Research of Tuva, 2019)
The article is a summarizing work identifying the specificity of the Kalmyk system of kinship terms as a lexical microsystem in relation to the distribution of its individual nominal units, as well as those semantic features that form lexical oppositions within this system and determine its historical and typological dynamics, in comparison with the kinship terminology system of the Tuvans. The paper explains reasons for similarities and differences between kinship terms of Mongolic (namely, Oirat) and Turkic peoples through the examples of kinship relations inherent to the Kalmyks and Tuvans, and considers the interaction of terms denoting kinship and affinity of Turkic and Mongolic origin within Tuvan-language discourse.It is noted that the explanation of the observed lexical similarities of the Turkic and Mongolic languages exclusively as contact phenomena in the light of facts from the history of Turkic languages as such is far less reliable than the explanation of the same similarities as a consequence of genetic relationship of the Altaic languages, though in the context of a certain number of cross-borrowings. The kinship terminology of Erzin Tuvans contains distinct traces of language contacts with the Oirat-Mongols. The Kalmyk system of kinship terms is characterized by a strict correlation of kinship terms by gender both in ascending and descending lines, the presence of a special lexical unit for nominating maternal relatives, and kinship counting up to the 9th generation in both ascending and descending lines while other Mongolic peoples take into account the kinship only up to the 5th generation in the ascending line and the 4th generation in the descending line respectively.
Keywords: Tuvans; Kalmyks; Oirat world; kinship terminology; componential analysis; ethnocultural contacts